Paramyxoviruses: biology & pathogenesis - Lee, Benhur (Henry Stewart Talks, 2024)
Classification of paramyxoviruses, Nipah and Hendra virus -Characteristic features of paramyxoviruses, Interferon antagonism, Paramyxovirus life cycle, Fusion protein (F) and receptor binding protein (RBP), Models for paramyxovirus fusion activation, Paramyxovirus receptors, Receptor tropism and Nipah virus pathogenesis